Pengendalian Pemanfaatan Tata Ruang dalam Sistem Zonasi Pembangunan Hotel Melalui Perijinan Kabupaten Badung - Alda Vidia Vergionita; I Nyoman Gede Sugiartha; Ida Ayu Putu Widiati (Jurnal Konstruksi Hukum, 2022)
The building structure states the existence of a sacred area in each of these hotels and villas. After being investigated and plugged into the direct location, there are indeed, however, the sacred area seems very far from the reach of the community and very close to the swimming pool. Because of a permit that can be violated issuing and grating permits in the construction of hotels and villas in the education area. From this problem, the formulation of the problem that occurs is how effective is the application of sanctions for violators of the use of Spatial Planning in hotel development in the Badung regency? What are the obstacles in implementing spatial zoning through the construction of licensed hotels in the Badung Regency? The type of research used in this research is empirical juridical research, considering that this research uses data or facts that exist in the field and is studied based on laws and regulations related to the issues raised. The results of this study indicate that the responsibility for laying spatial layouts is detrimental to the community in the district where the area is used as a means for education, not a means of tourism and the like.